2009
DOI: 10.1038/nprot.2009.191
|View full text |Cite
|
Sign up to set email alerts
|

Protocols to detect senescence-associated beta-galactosidase (SA-βgal) activity, a biomarker of senescent cells in culture and in vivo

Abstract: Normal cells can permanently lose the ability to proliferate when challenged by potentially oncogenic stress, a process termed cellular senescence. Senescence-associated beta-galactosidase (SA-betagal) activity, detectable at pH 6.0, permits the identification of senescent cells in culture and mammalian tissues. Here we describe first a cytochemical protocol suitable for the histochemical detection of individual senescent cells both in culture and tissue biopsies. The second method is based on the alkalinizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
1,104
2
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,344 publications
(1,134 citation statements)
references
References 34 publications
22
1,104
2
6
Order By: Relevance
“…69 Briefly, compound-treated MCF7 cells were fixed in 2% formaldehyde and 0.2% Caspase assay. MCF7 cells in a 6-well plate were treated with GTC365 for 48 h. The caspase-3/7 assay was conducted using DEVD-AFC as a substrate of capase-3/7.…”
Section: Senescence β-Galactosidase Assaymentioning
confidence: 99%
“…69 Briefly, compound-treated MCF7 cells were fixed in 2% formaldehyde and 0.2% Caspase assay. MCF7 cells in a 6-well plate were treated with GTC365 for 48 h. The caspase-3/7 assay was conducted using DEVD-AFC as a substrate of capase-3/7.…”
Section: Senescence β-Galactosidase Assaymentioning
confidence: 99%
“…an intracellular green-blue, insoluble precipitate, using the Senescence Detection Kit b-Gal (Calbiochem, QIA117) [11].…”
Section: Histologymentioning
confidence: 99%
“…Upon 3 days of culture in the presence of erlotinib, HME and HBE cells appeared morphologically similar to those deprived of EGF, failed to proliferate, and contained high SA-β-gal activity ( Figure 1D and 1E, Supplementary information, Figure S1F and S1G), indicating that EGF suppresses senescence by activating EGFR in these cell types. To quantify the level of senescence induced by EGFR inhibition, we made use of C 12 FDG, a substrate that becomes fluorescent after SA-β-gal-catalyzed cleavage [3]. Incubation with C 12 FDG and subsequent analysis by flow cytometry revealed that ~70% of HME and HBE cells were senescent after two days of treatment with 1 µM erlotinib ( Figure 1F-1H and Supplementary information, Figure S1H-S1J).…”
mentioning
confidence: 99%